2020
DOI: 10.26415/2572-004x-vol4iss1p518-519
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Biofilm Formation of Klebsiella Pneumoniae Isolated from Medical Devices at the University Hospital of Tlemcen, Algeria

Abstract: Background: Klebsiella pneumoniae is a major cause of community-acquired and nosocomial infections. This germ is responsible for acute and chronic infections, most of which are due to its ability to adhere to medical implants and form a biofilm. The objective of this work is to study the interaction between clinical isolates of K. pneumoniae and abiotic surfaces (medical devices) and some factors influencing biofilm formation. Methods: Over a period of 2 years, 115 strains of K. pneumoniae were isolated from m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…The MBEC assay also confirms the findings, as C3, C5, C6 and C8 strains showed an increase from MICs of ≤ 0.03 µg/ml (planktonic cells) to 2, 32, 128 and 4 µg/ml, respectively for biofilms. These susceptibility results of carbapenem on the fully-grown biofilm structure were consistent with the previous reports for gentamicin, cefotaxime and ciprofloxacin, amikacin and piperacillin in K. pneumoniae [18,19] . MBEC assays further revealed that the planktonic cells released from biofilm structure exhibited the same MICs as the biofilm cells, which might possibly be a mechanism for establishment of mobile resistant population in vivo causing clinical failure.…”
Section: Discussionsupporting
confidence: 92%
“…The MBEC assay also confirms the findings, as C3, C5, C6 and C8 strains showed an increase from MICs of ≤ 0.03 µg/ml (planktonic cells) to 2, 32, 128 and 4 µg/ml, respectively for biofilms. These susceptibility results of carbapenem on the fully-grown biofilm structure were consistent with the previous reports for gentamicin, cefotaxime and ciprofloxacin, amikacin and piperacillin in K. pneumoniae [18,19] . MBEC assays further revealed that the planktonic cells released from biofilm structure exhibited the same MICs as the biofilm cells, which might possibly be a mechanism for establishment of mobile resistant population in vivo causing clinical failure.…”
Section: Discussionsupporting
confidence: 92%
“…The strain used in this experience was isolated from urinary catheter and endotracheal tubes from the services of Intensive Care, Urology, and Neurology, at the University Hospital of Tlemcen. This strain was a high biofilm producer on inert surfaces as described previously by [78].…”
Section: Antibiofilm Activitymentioning
confidence: 99%
“…Gram nega ve isolates were further iden fied by different biochemical tests like oxidase, catalase, mo lity, indole and H S produc on, MR-VP, citrate u liza on, urea hydrolysis, 2 triple sugar iron u liza on tests. The iden ty of bacteria was, thus, established based as described in the book of 13 Cheesbrough.…”
Section: Sample Cultureand Iden Fica On Of Organismsmentioning
confidence: 99%